2014
DOI: 10.1590/s1806-83242014.50000003
|View full text |Cite
|
Sign up to set email alerts
|

Histological analysis of biocompatibility of ionomer cements with an acid-base reaction

Abstract: histological analysis of biocompatibility of ionomer cements with an acid-base reaction abstract: The purpose of this study was to evaluate the inflammatory and cure events of acid-based reactions using glass ionomer cement used for cementation of crowns, bridges, onlays and orthodontic bands implanted in subcutaneous tissue, at different time intervals. A total of 48 male Wistar rats were used, distributed into 4 groups (n = 12), as follows: Group C (control, polyethylene), Group ME (Meron), Group KC (Ketac C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
3
21
0
Order By: Relevance
“…The rats were anesthetized with an injection of ketamine (Konig S.A., São Paulo, SP, Brazil) and xylazine (Konig S.A., São Paulo, SP, Brazil) administered intramuscularly (Pinto et al, ). Subsequently, trichotomy of the surgical area and local asepsis with 4% chlorhexidine digluconate were performed (Dos Santos et al, ; Santos et al, ).After this, a straight line incision measuring approximately 20 mm was made with a No. 15 scalpel blade (Embramac, Itapira, Brazil) adapted to a scalpel handle, until the periosteum was reached.…”
Section: Methodsmentioning
confidence: 99%
“…The rats were anesthetized with an injection of ketamine (Konig S.A., São Paulo, SP, Brazil) and xylazine (Konig S.A., São Paulo, SP, Brazil) administered intramuscularly (Pinto et al, ). Subsequently, trichotomy of the surgical area and local asepsis with 4% chlorhexidine digluconate were performed (Dos Santos et al, ; Santos et al, ).After this, a straight line incision measuring approximately 20 mm was made with a No. 15 scalpel blade (Embramac, Itapira, Brazil) adapted to a scalpel handle, until the periosteum was reached.…”
Section: Methodsmentioning
confidence: 99%
“…9 Many authors suggest their high biocompatibility. [10][11][12][13] However, there are reports noting an adverse effect of these materials on live cells.…”
mentioning
confidence: 99%
“…The complete absence of these cells indicated that the biomaterials had low potential to induce foreign body giant cell reactions. This type of granulomatous tissue reaction has been related for resin-modified glass ionomer cement (17) and some ionomer cements with an acid-base reaction (22,23).…”
Section: Discussionmentioning
confidence: 95%